LOCAL PUBLIC SERVICE PROVISION, BUDGET ALLOCATION AND ECONOMIES-OF-SCALE: THE CASE STUDIES OF NORTHERN SUBDISTRICT ADMINISTRATIVE ORGANIZATIONS - Patmasiriwat, Direk; Stargell, Pawinee (RMUTT Global Business and Economics Review, 2022)
This paper presents an empirical analysis on theme of local public service provision and budget allocation of 474 subdistrict administrative organizations (SAOs) in 17 northern provinces with the data sources compiled by the Decentralization Office as of FY2564. This data source contains useful information such as budget allocation and provision of local public services grouped into 5 functions, namely, infrastructure, welfare for elderly, disable and HIVs victims, child and education, environment, and others. In addition to descriptive statistics and comparative statistics, this paper reports an econometric model in which budget amount and budget share are dependent variables and they are tested against the set of explanatory variables, such as population, elderly population, child population. In addition, the economies-of-scale is tested. The findings are summarized: (i) the per capita budget is on average about 2,743 baht per person (ii) the total budget increases at a decreasing rate as the number of populations increases. The elasticity is 0.847, meaning that a 10 percent increase in population affects 8.47 percent budget increase. In discussion, we propose the consolidation of small-sized SAOs among themselves or annex with larger local administrations nearby, with an expectation of a gain in efficiency in accordance with economies of scale.